A side-sensitive modified group runs double sampling (SSMGRDS) control chart for detecting mean shifts. Issue 5 (28th May 2018) - Saha, Sajal; Khoo, Michael B. C.; Lee, Ming Ha; Castagliola, Philippe
ABSTRACT: A side-sensitive modified group runs double sampling (SSMGRDS) chart for detecting mean shifts is proposed. The average number of observations to signal (ANOS) and expected average number of observations to signal (EANOS) performances of the SSMGRDS, , double sampling (DS), side-sensitive group runs double sampling (SSGRDS), side-sensitive modified group runs (SSMGR) and exponentially weighted moving average (EWMA) charts are compared. For the zero-state case, the SSMGRDS chart outperforms all charts under comparison, for all sizes of mean shifts. For the steady-state case, the EWMA chart prevails for small and moderate mean shifts but the SSMGRDS chart prevails for large shifts.